Residual Impact of Concurrent, Resistance, and High-Intensity Interval Training on Fasting Measures of Glucose Metabolism in Women With Insulin Resistance - Alvarez, Cristian; Ciolac, Emmanuel Gomes; Guimarães, Guilherme Veiga; Andrade, David C; Vasquez-Muñoz, Manuel; Monsalves-Álvarez, Matías; Delgado-Floody, Pedro; Alonso-Martínez, Alicia M.; Izquierdo, Mikel (Frontiers in Physiology, 2021)
We sought to assess the residual effects (post 72-h training cessation) on fasting plasma glucose (FPG) and fasting insulin (FI) after 12-weeks of high-intensity interval training (HIIT), resistance training (RT), or concurrent training (CT) in women with insulin resistance (IR). We also aimed to determine the training-induced, post-training residual impact of CT. A total of adult 45 women (age 38.5±9.2years) were included in the final analysis and were assigned to a control (CG; n=13, BMI 28.3±3.6kg/m2), HIIT [n=14, BMI 28.6±3.6kg/m2, three sessions/wk., 80–100% of the maximum heart rate (HRmax)], RT [n=8, BMI 29.4±5.5kg/m2, two sessions/wk., 8–10 points of the modified Borg, corresponding to 20 to 50% range of one maximum repetition test (1RM)], or CT group (n=10, BMI 29.1±3.0kg/m2, three sessions/wk., 80–100% of HRmax, and 8–10 Borg, or 20 to 50% range of 1RM, to each HIIT and RT compounds), with the latter including both HIIT and RT regimens. Training interventions lasted 12-weeks. The main outcomes were FPG and FI measured at pre- and 24-h and 72-h post-training (FPG24h, FI24h, and FPG72h, FI72h, respectively). Secondary endpoints were body composition/anthropometry and the adiposity markers waist circumference (WC) and tricípital skinfold (TSF). The residual effects 72-h post-training [delta (∆)] were significantly poorer (all p<0.01) in the CT group (∆FPG72h+6.6mg/dl, η2: 0.76) than in the HIIT (∆FPG72h+1.2mg/dl, η2: 0.07) and RT (∆FPG72h+1.0mg/dl, η2: 0.05) groups. These findings reveal that HIIT reduces FPG and RT reduces FI 24-h post-training; both exercise interventions alone have remarkably better residual effects on FPG and FI (post-72h) than CT in women with insulin resistance.